Βελτίωση διεργασιών εργαστηρίου ελέγχου ποιότητας και εφαρμογή εργαλείων διασφάλισης ποιότητας σε μεταλλοβιομηχανία - Καράσαββας, Στέλιος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The metal industry constantly tests the produced materials in order to ensure that their production meets both the international ISO standards and EU directives. Hence, this dissertation aims to assess the quality of production of a national metal company by analysing historical data from tests conducted for two materials. In particular, this dissertation assessed the quality of both the products and the laboratory of quality control of the Cypriot company Nicolaides & Kountouris Metal Company Ltd. This research was conducted at the premises of the company. Subsequently, on the basis of the principles of Total Quality, various parameters were assessed and the most important ones were selected for improvement with the help of appropriate quality tools and Statistical Quality Control. The data used in this dissertation were the tests of both the polyurethane panels and thermal insulation polyurethane cements for the last 3 years. The following variables were used: the density, thermal conductivity and compression resistance. The values were compared to those suggested by the international ISO standards, EU directives and those of the company’s target using statistical analysis. The analysis was conducted using the software SPC IV Excel. Such results can be used by the industry in order to investigate the reasons that a segment failed the test and make the appropriate improvements.
Keywords: Total quality; Statistical quality control; Process control; Process control charts; Μεταποιητική βιομηχανία; Στατιστικός έλεγχος διεργασιών; Ολική ποιότητα